Persepsi Pelajar Terhadap Persekitaran Fizikal Makmal Komputer : Perbandingan Antara Dua Makmal Komputer Yang Berbeza Susun Atur - Salleh, Nurizah; Mohd Ayub, Ahmad Fauzi; Zainal Abidin, Norhasni (Journal of Techno-Social, 2010)
The used of computers is increasingly becoming important in Malaysian education system. This occurs due to the rapid development of information technology in the world. Every educational policy that is planned involves the integration of information and communication technology. This computer usage is related to the computer laboratory. Hence, the computer laboratory should be well designed so that it will create a conducive learning environment. This study is to identify students’ perception towards the physical of computer laboratory, social interaction and students innovation received by the students in a pair computer laboratory and pod arrangement computer laboratory. A total of 115 students were involved consisting of 53 students using pair computer laboratory for practical classes and 62 students using the pod arrangement computer laboratory. Statistical analysis shows that there are significant differences in the mean of physical computer laboratory environment for pair computer laboratory (t(113) = 2.704, p=.008<0.05) and innovation students (t(113)= 3.063, p= .003 < .05) compared to the pod arrangement computer laboratory. However there is no significant differences in mean of social interaction (t(113)=0.464, p=0.643 > .05). This study provides implications that different computer labs in terms of layout will affect the physical environment of innovation and student computer labs. The selection of the computer laboratory layout should be able to promote social interaction while in the computer laboratory and help students to be more innovative and creative during practical in the computer laboratory.